Basalt Fibers in Modified Whisker Reinforced Cementitious Composites - Khan, Mehran; Cao, Mingli; Ai, Hongmei; Hussain, Abasal (Periodica Polytechnica Civil Engineering, 2022)
The calcium carbonate whisker (CW) and basalt fiber are gaining popularity due to its enhanced mechanical properties in composites. Also, the short and long fibers provide bridging role and resistance against cracking from micro- to macro-scale, respectively. The usage of long and short hybrid basalt fiber along with addition of CW in cement-based composites is still a research gap. In this work, experimental behavior of CW basalt hybrid fiber reinforced mortar is considered with various content and length (3 mm, 6 mm, 12 mm, and 20 mm) of hybrid basalt fibers. In addition to this, synergy performance index is determined to quantitatively evaluate the positive interaction of hybrid basalt fiber in cementitious materials. The strengthening effect of whiskers and basalt fibers are also studied using scanning electron microscopy. The CW with various basalt fiber contents having different length of hybrid basalt fiber is used. It was found that the four various length of hybrid basalt fiber together with CW in cement mortar exhibited enhanced compressive, flexural, and split tensile strength than that of pure mortar and single length basalt fiber reinforced cementitious mortar. The results of synergy performance index showed similar trend with the experimental results. The strengthening effect caused by step by step crack arresting mechanism was also observed in cementitious material.